2015
DOI: 10.1016/j.drugalcdep.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic binge-like ethanol consumption on cocaine self-administration in rhesus monkeys

Abstract: Background Most cocaine abusers also abuse alcohol, but little is known about interactions that promote co-abuse. These experiments in rhesus monkeys determined the effects of >8 weeks of ethanol (EtOH) consumption on cocaine self-administration (n=6), effects of dopamine (DA) receptor antagonists on cocaine reinforcement (n=3–4 per drug) and the ability of the D2-like DA receptor agonist quinpirole to elicit yawning (n=3). Methods Monkeys self-administered cocaine (0.0–1.0 mg/kg/injection, i.v.) under a 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…Furthermore, self-administered cocaine did not affect BECs, consistent with human studies (Farré et al 1993, 1997; Higgins et al, 1993; McCance-Katz et al 1993; Perez-Reyes and Jeffcoat 1992). These results extend previous preclinical animal research investigating the interactions of intravenous EtOH and cocaine (Aspen and Winger, 1997; Czoty, 2015, 2016; Winger et al, 2007) to intragastric administration of EtOH and to a schedule of cocaine self-administration that utilized conditioned stimuli to maintain drug seeking.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Furthermore, self-administered cocaine did not affect BECs, consistent with human studies (Farré et al 1993, 1997; Higgins et al, 1993; McCance-Katz et al 1993; Perez-Reyes and Jeffcoat 1992). These results extend previous preclinical animal research investigating the interactions of intravenous EtOH and cocaine (Aspen and Winger, 1997; Czoty, 2015, 2016; Winger et al, 2007) to intragastric administration of EtOH and to a schedule of cocaine self-administration that utilized conditioned stimuli to maintain drug seeking.…”
Section: Discussionsupporting
confidence: 78%
“…Czoty (2015) reported that in monkeys self-administering cocaine under an FI 5-min schedule of reinforcement, 1.0 g/kg EtOH (i.v.) significantly decreased reinforcement frequency when a low dose of cocaine was self-administered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of other licit and illicit substances on cocaine use has received even less attention. However, those studies that have modeled polysubstance abuse in animals have identified drug interactions that can enhance cocaine reinforcement (e.g., Mattox et al, 1997;Mello et al, 556 2014;Czoty, 2015). Severity of cocaine use (in terms of duration or total lifetime doses) could also be incorporated as an independent variable, particularly in animal laboratory studies where pharmacological variables can be easily controlled.…”
Section: E Overall Conclusion and Recommendationsmentioning
confidence: 99%